Letter (copy) : Spanish Fund - Parkin, E. G.
028-0204-001 EP/LK/EK/470. Finance. 3rd September, 1936. Mr. H. V. Tewson, The Royal Hotel, Plymouth, Devon. Dear Mr. Tewson, SPANISH FUND. Will you kindly sign the enclosed receipt and have it sent to the National City Bank of New York in Bishopsgate. Regarding our official receipt this has been made out to Mr. Dubinsky, and as I presume he will be written after Congress the receipt itself will be filed for the present. Yours sincerely, Receipt. 292/946/28/204